Congenital cataract: A case report of two sisters - Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
Two sisters suffering from bilateral congenital zonular cataract have been reported-. Their parents and their one and only sister were perfectly normal. The older sister was 2 years old whereas the younger was 8 months when they were first examined and they immediately underwent discission and evacuation. It was likely that the two cases carried autosomal dominant genes for congenital zonular cataract, either non-penetrant genes or a fresh mutation of the germ cell of one of their parents. In the former the recurrence risk was 50%, whereas in the latter such risk was practically zero. Key Words: congenital zonular cataract - autosomal dominance - non-penetrant gene - fresh mutation - recurrence risk